Losing the 'arms race': multiresistant salmon lice are dispersed throughout the North Atlantic Ocean. Issue 5 (26th May 2021) - Fjørtoft, Helene Børretzen; Nilsen, Frank; Besnier, Francois; Stene, Anne; Tveten, Ann-Kristin; Bjørn, Pål Arne; Aspehaug, Vidar Teis; Glover, Kevin Alan
Abstract : Nothing lasts forever, including the effect of chemicals aimed to control pests in food production. As old pesticides have been compromised by emerging resistance, new ones have been introduced and turned the odds back in our favour. With time, however, some pests have developed multi-pesticide resistance, challenging our ability to control them. In salmonid aquaculture, the ectoparasitic salmon louse has developed resistance to most of the available delousing compounds. The discovery of genetic markers associated with resistance to organophosphates and pyrethroids made it possible for us to investigate simultaneous resistance to both compounds in approximately 2000 samples of salmon lice from throughout the North Atlantic in the years 2000–2016. We observed widespread and increasing multiresistance on the European side of the Atlantic, particularly in areas with intensive aquaculture. Multiresistant lice were also found on wild Atlantic salmon and sea trout, and also on farmed salmonid hosts in areas where delousing chemicals have not been used. In areas with intensive aquaculture, there are almost no lice left that are sensitive to both compounds. These results demonstrate the speed to which this parasite can develop widespread multiresistance, illustrating why the aquaculture industry has repeatedly lost the arms race with this highly problematic parasite.